PESAN DAKWAH DALAM PODCAST YOUTUBE KOPIPANAS.CHANNELS EDISI #2 CAFEKITA – ULAS BUKU-CINTANYA HATI SUHITA - Husnul Inayah, Hasna; Slamet, Moh. (Universitas Hasyim Asy'ari, 2024)
In this advanced and modern era, the activities of Islamic preaching (dakwah) have adapted to the current developments, particularly through the sophistication of social media. This study examines the preaching messages found in the YouTube Podcast titled